Estudio de Factibilidad para la Creación de una Aplicación Informática para las Personas con Discapacidad Auditiva - Rumiguano Tamami, Rolando Jaime (2017)
Labor Integration Service - City of Babahoyo. It is an institution that provides training and talks, among the main drawbacks of the institution is the lack of computer technology and trained personnel to provide sign language service for hearing impaired people in the city of Babahoyo. From a medical-physiological point of view, in relation to hearing loss is the decrease in listening abilities, people with this problem not only listen less, but also that the sounds are regular and distorted by eliminating the possibilities in the process duly received information. For some authors it is the only alternative that allows access to a job integrity through a mobile application applying instruction for the use of these people. Being so is one of the most important means, where the code is understandable limiting the conditions of good communication. It can be identified that the technological equipment has changed because the institution is not assigned a professional with special disabilities, reason why the authorities do not receive any type of training that manages to improve the process of teaching-learning. As the institution does not have the appropriate computer tools for the hearing impaired, it is proposed in the future to develop a didactic mobile application adapted to the special needs of people with disabilities of the institution (SIL). So that people in this way have pedagogical tools that collaborate to improve academic performance in an understandable and entertaining way.